THE EFFECT OF ORGANIZATIONAL CULTURE AND COMPENSATION ON JOB SATISFACTION AND EMPLOYEE PERFORMANCE AT PT. PEGADAIAN KENDARI BRANCH IN KENDARI CITY - Patiung, Zakaria Bangka’; Alam, Syamsu; Pono, Maat (Scientia Integritas Utama, 2022)
Employee performance is a factor that plays an important role in achieving company and individual goals. If the people in the company are not performing well, the company will have a hard time achieving its goals. Employees must be knowledgeable, devoted, submissive, disciplined, and accountable for every job performed and completed in order to meet organizational goals. Companies, especially governmental organizations, should ideally develop organizational culture so that employees have values, norms, references, and principles that must be followed. This study sought to ascertain how organizational culture and pay affected employee performance and satisfaction at PT Pegadaian Kendari Branch in Kendari City. In this study the population numbered 33 people because the population was small, so the authors took a saturated sampling technique so that the sample size was also 33 people. Path analysis is the analytical technique utilized. The findings of this study show that organizational culture and compensation factors significantly and favorably affect employee performance as measured by job satisfaction.